Marconi, masculinity and the heroic age of science: wireless telegraphy at the British Association meeting at Dover in 1899. (2nd April 2016) - Ellis, Heather
Abstract: In September 1899, at the annual meeting of the British Association for the Advancement of Science (BAAS) in Dover, Guglielmo Marconi's wireless telegraphy system was used to transmit messages across the English Channel (and across a national border) for the first time. This achievement represented a highly effective performance of scientific masculinity and constitutes a key turning point in an important struggle between competing interpretations of invention and innovation as masculine practices within British science. The British Association tended to favor a narrative of scientific research as a collectivist, international, gentlemanly-amateur pursuit, largely confined to the laboratory. Marconi, by contrast, explained the development of wireless telegraphy as the achievement of his own genius. Appealing not only to the established scientific elite but to a range of non-traditional audiences, and stressing the possibilities or 'imagined uses' of his technology even more so than his actual results, he succeeded in commanding unprecedented influence.